Puppets as a learning experience to teach vocabulary in 5th grade (2021)
The following classroom project was carried out with a fifth-grade group from a public school in Santa Rosa de Cabal, Colombia. This project had an objective to promote and report the effects of puppets to teach vocabulary, since the school is in the process of becoming bilingual. The project was implemented in ten interventions of two hours each where students built their own puppets while learning new vocabulary related to the topic lesson in each class and learned to set a puppet performance. The instruments to gather the information from the interventions were the practitioners’ journals, observations and students artifacts to register information related to students reactions, linguistic outcomes and practitioners professional growth. The expected results at the end of the implementation, students were to expand their vocabulary repertoire in the second language through the practice; besides, taking as a reference the suggested curriculum, it was expected that students may improve their skills in listening and speaking through the exercise of listening and express themselves through the puppet.